Application of drug-induced sleep endoscopy in predicting the outcomes of velopharyngeal surgery in adult patients with Friedman stage II and III obstructive sleep apnea syndrome - Cao, Xin; Zhou, Yingqian; Zhang, Junbo; Yin, Guoping; Ye, Jingying (Frontiers in Neurology, 2023)
Objective This study aimed to evaluate the predictive value of drug-induced sleep endoscopy (DISE) for the outcomes of velopharyngeal surgery in adult patients with Friedman stage II and III obstructive sleep apnea syndrome (OSAS). Methods A total of 39 male OSAS patients with Friedman stage II and III were retrospectively analyzed. Subjects with an apnea-hypopnea index (AHI) > 5 events/h indicated by polysomnography (PSG) and typical symptoms, such as snoring, sleep apnea, and daytime sleepiness, were included in this study. All these patients underwent pre-operative DISE examinations and were treated by velopharyngeal surgery and evaluated by velum, oropharynx, tongue base, and epiglottis (VOTE) scoring system. Clinical, polysomnographic parameters (e.g., hypopnea, apnea, AHI, lowest oxygen saturation, etc.), cephalometric variables, and DISE findings were evaluated. The treatment outcomes were assessed by polysomnography at least 6 months after surgery. Results All 39 patients showed complete velopharyngeal airway collapses during pre-operative DISE examinations. After surgery, the AHI was significantly improved from 50.2 ± 21.6 to 19.8 ± 19 events/h (P < 0.05). There were 23 responders (59.0%) and 16 non-responders (41.0%). The glossopharyngeal airway collapse degree (GA-CD) was significantly different between responders and non-responders (P < 0.05). The velopharyngeal airway collapse pattern (VA-CP) and GA-CD were independently predictive of treatment outcomes (both P < 0.05). Patients with non-lateral VA-CP and grade II GA-CD (collapse degree > 50%) had a significantly lower surgical success rate than those without (P < 0.05). Conclusion The VA-CP and GA-CD in DISE examination are valuable for predicting the treatment outcomes of velopharyngeal surgery in patients with Friedman stage II and III OSAS. Patients with lateral VA-CP and grade I GA-CD are appropriate candidates for velopharyngeal surgery.